Pengembangan Prototype Sistem E-Commerce pada Ajun Elektronik dengan Metode FAST - Sarwindah Sarwindah; Elly Yanuarti (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
While the development of information technology is very influential for the progress of a business, promoting a business that is owned, then one of them by using an ecommerce website. E-commerce is a trading activity carried out online through a website. Problems in electronic adjunct stores Stores still use a conventional system where if a buyer wants to buy the desired item, the buyer must come directly to the store and this condition makes marketing and sales hampered by distance and time. In addition, the promotion at Arjun Electronics Store has not been fully implemented properly because it is only done by directly informing buyers who come to the shop. the purpose of this research is to produce a system that can provide ease of introducing products in the electronic adjuncts and sell all electronic products for household needs. With e-commerce site that is able to provide information about goods to customers quickly through internet network technology. Where asthe FAST method is a fairly flexible framework for various types of projects and strategies. System development with the FAST method is carried out sequentially which includes the stages of scope definition, problem analysis, needs analysis, logical design, decision analysis, physical design and integration, construction and testing, insralation and delivery, The results of this study in the form of website-based e-commerce optimization. With this website, stores can expand marketing, consumers become easier to get information about goods without having to come to the Electronic Adjunct Store and with the (e-commerce), the store can facilitate the conventional transaction process that has been conventional to be modern and can certainly make it easier to create sales reports that were previously still manual.